1992
DOI: 10.3109/10826089209068770
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cocaine Dependence in Methadone Maintenance Clients: A Pilot Study Comparing the Efficacy of Desipramine and Amantadine

Abstract: We conducted a pilot study (N = 22) comparing the efficacy of desipramine and amantadine for treatment of cocaine dependence in methadone maintenance clients. The study which lasted 12 weeks, was double-blind, randomly assigned, and placebo-controlled. Subjects met DSM-III-R criteria for active cocaine dependence. All three groups' cocaine use, craving, and depressive symptoms declined significantly, but intergroup differences were not significant. Clients receiving desipramine were significantly more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…This result favored desipramine, but it was statistically non‐significant (RR = 0.82; 95% CI 0.6–1.13). When trials were analysed separately according to the presence of an additional diagnosis of opioid dependence, the result on heterogeneity held for the studies, including patients on methadone maintenance treatment (Kolar et al. 1992; Kosten et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result favored desipramine, but it was statistically non‐significant (RR = 0.82; 95% CI 0.6–1.13). When trials were analysed separately according to the presence of an additional diagnosis of opioid dependence, the result on heterogeneity held for the studies, including patients on methadone maintenance treatment (Kolar et al. 1992; Kosten et al.…”
Section: Resultsmentioning
confidence: 99%
“…= 1; P = 0.04). A small RCT ( n = 17) (Kolar et al 1992) showed an extremely non‐significant positive result favoring desipramine (RR = 0.16; 95% CI 0.02–1.04). The results for trials with primary cocaine dependence patients were more homogeneous, with no significant differences between desipramine and placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological modulation of the dopamine (DA) system has been the most common approach. Three types of dopaminergic modulation have been studied: direct agonism using amantadine (33,36,37) or bromocriptine (34), indirect agonism using bupropion (40,50), dexamphetamine (32), disulfiram (28,47), or mazindol (41,42), and antagonism using risperidone (32). Indirect noradrenergic agonism using desipramine to block the noradrenaline (NA) reuptake transporter has also been widely studied (23,36,37,39,45).…”
Section: Efficacy Of Adjunctive Interventions To Omt For Dual Heroin-mentioning
confidence: 99%
“…Three types of dopaminergic modulation have been studied: direct agonism using amantadine (33,36,37) or bromocriptine (34), indirect agonism using bupropion (40,50), dexamphetamine (32), disulfiram (28,47), or mazindol (41,42), and antagonism using risperidone (32). Indirect noradrenergic agonism using desipramine to block the noradrenaline (NA) reuptake transporter has also been widely studied (23,36,37,39,45). Other pharmacological strategies such as serotonin reuptake inhibition using fluoxetine (31), GABAergic agonism using tiagabine (29,30) or gabapentin (30), cortisol inhibition (38), nicotine antagonism (52), and magnesium (43) have been infrequently studied.…”
Section: Efficacy Of Adjunctive Interventions To Omt For Dual Heroin-mentioning
confidence: 99%
“…It has been reported that methadone raises blood levels of desipramine thereby making for complicated dosing of desipramine to control cocaine use and cocaine craving (Kosten et al 1987). Nevertheless, there is some strong evidence that desipramine and amantadine may be helpful in reducing cocaine use, craving, and depressive symptoms in a group of methadone maintenance patients and that desipramine may be helpful in keeping patients in treatment and cocaine-free at the end of the study (Kolar et al 1993).…”
Section: Treating Patients Who Are Codependent or On Other Medicationmentioning
confidence: 99%